Pengaruh Kesenjangan Pendidikan terhadap Pola Pikir Siswa SMA dan Mahasiswa: Analisis Kuantitatif dari Trend Tiktok di Indonesia - Kartika, Sintiya; Sarah, Siti; Simbolon, Puspita; Ajri, Munajmi; Nursiah; Hakim, Saif Eldi; Nabilla, Putri Sukma; harahap, Nursapia (Al-Wasathiyah: Journal of Islamic Studies, 2024)
The study focuses on the impact of educational disparities on the mindset of high school students and students in Indonesia. In this study, the analysis uses quantitative data from TikTok trends in Indonesia to understand how education disparities affect the way students think between high school and students. Studies show that educational gaps have a significant impact on the mindset of both high school students and students. High school students who have good access to education have a more positive mindset and are better prepared to adapt to change, while students with better access to school have more critical mindsets and are more ready to think analytically. The results of this research have important implications for educational policy in Indonesia, as well as to raise public awareness of the importance of educational equality in improving the thinking ability of students.